Consensus on diagnostic criteria for Alzheimer's disease. - LI, Yan-feng; JI, Yong (Chinese Journal of Contemporary Neurology & Neurosurgery, 2026)
With the escalating global aging population, Alzheimer's disease (AD) has imposed social and economic burden on public health systems worldwide. In recent years, significant advancements have been achieved in understanding the pathogenesis, diagnostic methods, and disease-modifying therapy (DMT), which simultaneously present new directions and challenges for clinical practice. Therefore, there is an urgent need to develop standardized protocols aligned with current clinical diagnosis and treatment requirements. By comprehensively searching Alzheimer's disease-related literatures, including Meta-analyses, systematic reviews, randomized controlled trials, and cohort studies, we adopted modified Grades of Recommendations Assessment Development and Evaluation (GRADE) system to grade the quality of evidence and strength of recommendations, the "Consensus on diagnostic criteria for Alzheimer's disease" has been compiled, integrating key application points of integrating multimodal techniques such as neuropsychological assessment, neuroimaging and biomarkers, while balancing clinical applicability with cutting-edge evidence, to propose a practical framework and expert recommendations for the standardized diagnosis of Alzheimer's disease.